A novel m7G methylation–related signature associated with chromosome homeostasis in patients with lung adenocarcinoma - Tao, Xiaoying; Huang, Run; Xu, Rujun; Zheng, Shuang; Yue, Juanqing (Frontiers in Genetics, 2022)
Lung adenocarcinoma (LUAD) is a malignant tumor of the respiratory system with poor prognosis. Recent studies revealed that N7-methylguanosine (m7G) methylation is a widespread modification occurring in RNA. But the expression of m7G methylation-related genes in LUAD and their correlations with prognosis are still unclear. In the paper, we found out 12 m7G methylation-related regulators with differential expression between LUAD and normal lung tissues. According to differentially expressed genes (DEGs), all LUAD cases were separated into 2 subtypes. The prognostic value of each m7G methylation-related gene for survival was evaluated to construct a multigene signature using The Cancer Genome Atlas (TCGA) cohort. Finally, a m7G methylation-related prognostic signature based on 3 genes was bulit to cllasify LUAD patients into two risk groups. Patients in the high-risk group showed significantly reduced OS compared with patients in the low-risk group (P < 0.05). Receiver operating characteristic (ROC) curve analysis confirmed predictive capacity of the signature. Gene Ontology (GO) functional annotation analysis disclosed chromosome homeostasis playing an important role in this process. Gene set enrichment analysis (ssGSEA) implied the immune status was decreased in the high-risk group. To sum up, m7G methylation related genes play a vital role in tumor immunity and the related signature was a reliable predictor for LUAD prognosis.